The Covid-19 pandemic in international law: A preliminary inquiry - Schiappa-Pietra, Oscar (2020)
The Covid-19 pandemic impinges upon various areas of international law, and calls into question the effectiveness of current organizational and regulatory frameworks for global governance. In particular, it reviews the rules on the human right to health, the powers of the World Health Organization, and the available international dispute resolution instruments to resolve controversies generated by the pandemic or by the measures adopted by governments to address it.